Aristotle and Augustine on Freedom - Chappell, T. author. aut Link
XIV, 214 p.
Keywords: Aristotle and Augustine both hold that our beliefs in freedom and voluntary action are interdependent, and that voluntary actions can only be done for the sake of good. Hence Aristotle holds that no-one acts voluntarily in pursuit of evil: such actions would be inexplicable. Augustine, agreeing that such actions are inexplicable, still insists that they occur. This is the true place in Augustine's view of his 'theory of will' - and the real point of contrast between Aristotle and Augustine.